Potential physiological responses contributing to the ergogenic effects of acute ischemic preconditioning during exercise: A narrative review - O’Brien, Liam; Jacobs, Ira (Frontiers in Physiology, 2022)
Ischemic preconditioning (IPC) has been reported to augment exercise performance, but there is considerable heterogeneity in the magnitude and frequency of performance improvements. Despite a burgeoning interest in IPC as an ergogenic aid, much is still unknown about the physiological mechanisms that mediate the observed performance enhancing effects. This narrative review collates those physiological responses to IPC reported in the IPC literature and discusses how these responses may contribute to the ergogenic effects of IPC. Specifically, this review discusses documented central and peripheral cardiovascular responses, as well as selected metabolic, neurological, and perceptual effects of IPC that have been reported in the literature.